Rancang Bangun Paper Pot Transplanter Portable Bawang Merah (Allium ascalonicum L.) - Legowo, Rizky; Zulkarnain, Iskandar; Rahmawati, Winda (Jurnal Agricultural Biosystem Engineering, 2022)
This study aims to design, build, and test the equipment. Therefore, the work capacity, the result of planting shallots, and the percentage of planting success were parametered measured in this study. The method used in this study includes designing, manufacturing, and testing. The design phase used  Solid Work softwere and followed by manufacturing building most of which use metal plate material. The next process is the testing phase which is carried out 5 times. After designing and manufacturing, then the shallots planting equipment is produced using paper chain pot with length 200 cm, width 35 cm, height 100 cm and weight 8 kg which is easy brought and disassembled according to user needs. This equipment is capable planting shallots with a uniform distance and faster than the concentional cultivate.  The test results showed that a paper pot transplanter portable shallots proved to be twice as effective in doing planting shallots. Has a working capacity of 15468,26 seeds/hour with uniform spacing of 5 cm x 15 cm and effective field capacity of 0,0102 ha/hour with a planting success percentage of 96,21%, compared to conventional planting has a work capacity of 2605,36 seeds/hour with a spacing of 10 cm x 15 cm and an effective field capacity of 0,0037 ha/hour and planting success percentage 98.86%.